The Role of Folk Oral Creativity in Children’s Literature - Ilhomjon, Ubaydullayev (European Journal of Life Safety and Stability (2660-9630), 2021)
Folk oral art is a kind of oral word art, which is distinguished by its distinctive features from other types of folk art, such as music, theater, dance, play, fine and Applied Art.